EXPERIENCE OF VOUCHERS FOR REPRODUCTIVE HEALTH SERVICES IN DEVELOPING COUNTRIES: MAKING A CASE FOR PAKISTAN THROUGH A SYSTEMATIC REVIEW - Mehboob, Gulrukh; Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2015)
Among the healthcare financing techniques that exist, output-based financing or vouchers is a strategy that is growing in popularity. There is a need of an in-depth analysis of the impacts of vouchers on health indicators, particularly for Pakistan. Assessment of the existing evidence on how much the vouchers impact on health and healthcare utilization can be of greater value to the policy makers for informed decision making. This systematic review included 16 cross-sectional and quasi-experimental design studies. Service utilization, knowledge, service quality, cost-effectiveness of the programme and outreach of the population served were observed as outcomes. We found positive results in with regard to most of these outcomes. Physical accessibility, social mobility of women, security threats, and sustainability of the project after donor exit appear as serious challenges. Yet, lessons can be drawn for the scaling up of the reproductive health services in the country, through the use of vouchers.